2019
DOI: 10.1016/j.jacr.2019.02.028
|View full text |Cite
|
Sign up to set email alerts
|

ACR Appropriateness Criteria® Acute Hip Pain-Suspected Fracture

Abstract: Acute hip pain following a low-force trauma such as a ground-level fall is a common clinical problem. In the elderly osteoporotic population, this is frequently the result of fractures of the proximal femur or pelvis. As physical examination is often inconclusive, imaging is critical for diagnosis. Radiographs are the preferred first-line imaging modality, although their sensitivity is limited for nondisplaced fractures and further imaging may be necessary as discussed in this article and summarized in the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…This may include the ordering of diagnostic imaging exams such as x-rays, computed tomography (CT) scans, magnetic resonance imaging (MRI), or ultrasound. Although guidelines may exist for specific patient presentations [22][23][24], it is often up to the individual physician to decide how to proceed. This subjective assessment process is subject to potential bias that may lead to differential care for minority groups.…”
Section: Introductionmentioning
confidence: 99%
“…This may include the ordering of diagnostic imaging exams such as x-rays, computed tomography (CT) scans, magnetic resonance imaging (MRI), or ultrasound. Although guidelines may exist for specific patient presentations [22][23][24], it is often up to the individual physician to decide how to proceed. This subjective assessment process is subject to potential bias that may lead to differential care for minority groups.…”
Section: Introductionmentioning
confidence: 99%
“…Plain films provide an appropriate first line for assessing pelvic fractures, however, these can be relatively insensitive, particularly in osteoporotic patients (40). Sensitivities of approximately 70% have been reported with particular insensitivity for posterior fractures on anteroposterior pelvic radiographs.…”
Section: Plain Filmmentioning
confidence: 99%
“…26,27 Older adults with osteoporosis are at risk for occult fracture; specifi c risk factors for occult fracture include age over 65 years, low mechanism of injury, and female sex. 28 If initial plain radiographs are negative or equivocal, especially in older adults with persistent hip or groin pain, consider additional imaging modalities.…”
Section: Figure 1 Femoral Neck Fracturementioning
confidence: 99%
“…8 Several studies have shown that MRI has an accuracy at or near 100%. 25,27,28 A recent study of 1,248 patients by Kellock and colleagues found that CT was 94% sensitive. 29 This is higher than other studies, which found accuracies of CT ranging from 69% to 87%.…”
Section: Figure 1 Femoral Neck Fracturementioning
confidence: 99%
See 1 more Smart Citation